2270. Frequency of Syphilis Annual Screening Testing, Prevalence of Infection and Re-infection and Associated Characteristics among People Receiving Care for HIV in an HIV/AIDS Care Clinic in Mexico City (2001–2017). (26th November 2018) - Camiro-Zúñiga, Antonio; Escobedo-López, Kenia; De León Garduño, Alfredo Ponce; Pérez-Gutiérrez, Maria Teresa; Caro-Vega, Yanink; Crabtree-Ramírez, Brenda; Mora-Suarez, Nora K; Reyes-Romero, Monica; Ramos-Hinojosa, Ancelmo; Sierra-Madero, Juan G; Belaunzaran-Zamudio, Pablo Francisco
Abstract: Background: Syphilis has increased among people living with HIV (PLWH), particularly in men who have sex with men (MSM). Syphilis screening test should be routinely offered as part of comprehensive care for PLWH. We assessed the annual frequency of syphilis testing and positive test results in patients actively receiving care for HIV in Mexico City and its associated factors. Methods: We retrospectively analyzed cohort data of patients receiving care for HIV in our clinic (2001–2017). We estimated the annual proportion of PLWH receiving care that was tested for Syphilis and the annual prevalence of Syphilis infection among those tested. We performed annual, cross-sectional analysis in patients receiving care. We included patients with at least one registered visit to the clinic each year and defined those that were engaged in care, as those with at least two visits separated by at least 3 months in a given year. To identify factors associated with being tested and with being infected we used multivariate logistic regression models with random intercepts and GEE using sex, age, education, socioeconomic status (SES), year, time in care, use of ART, being naïve and having AIDS at enrollment, being engaged in care, and number of hospitalizations as independent variables. Results: 2896 patients were included. The proportion of patients tested for syphilis increased from 21% in 2001 to 81% in 2017. The prevalence of syphilis increased from 7% to 21% during the same period with an early peak in 2003–2004 (Figure 1). Over time, the prevalence of re-infections increased substantially and accounted for the most positive test from 2013 onwards. Men, younger age, MSM, increasing education, time receiving care, number of hospitalizations and being engaged in care during the year were positively associated with being tested (Figure 2). Men, younger age, MSM, patients not receiving ARTs, those with AIDS at enrollment, and not being engaged in care were at higher risk of infection (Figure 3). Conclusion: Annual VDRL testing increased over time, as did prevalence of syphilis, particularly after 2010 (9% vs. 21%). Re-infections were frequent. Efforts are needed to increase screening among women, those newly enrolled in care, and with low SES. Preventive strategies are needed for men, particularly MSM, early after enrollment. Disclosures: All authors: No reported disclosures.